Main Capabilities and Features of Ultra Wideband (UWB) Radars - Immoreev, I.J. (Радиофизика и радиоастрономия, 2002)
This review paper discusses the differences between ultra wideband (UWB) radars and the conventional narrow-band radars. The features are shown of the generation, radiation and processing of UWB radar signals evoked by the change of the signal waveform in the process of location, by appearance of the mutual dependence between the signal waveform and antenna directivity, and other. The possibility for the reception of the target radioimage is shown. В этой обзорной статье обсуждаются различия между сверхширокополосными радарами и обычными узкополосными. Приведены особенности генерирования, излучения и обработки сверхширокополосных радарных сигналов, связанные с изменением формы сигнала в процессе локации, в виде взаимозависимостей между формой сигнала и направленностью антенны и другими параметрами. Показаны возможности получения радиоизображения объекта. У даній оглядовій статті обговорено відмінності між надширокосмуговими радарами та звичайними вузькосмуговими. Наведено особливості генерування, випромінювання та обробки надширокосмугових радарних сигналів, пов’язані зі зміною форми сигналу в процесі локації, у вигляді взаємозалежностей між формою сигналу та спрямованістю антени та іншими параметрами. Продемонстровано можливості отримання радіозображення об’єкту.